Wound irrigation versus swabbing technique for cleansing noninfected chronic wounds: A systematic review of differences in bleeding, pain, infection, exudate, and necrotic tissue. Issue 1 (February 2023) - Rajhathy, Erin M.; Meer, Juliann Vander; Valenzano, Teresa; Laing, Leanna E.; Woo, Kevin Y.; Beeckman, Dimitri; Falk-Brynhildsen, Karin
Abstract: Purpose: To systematically summarize and review the existing literature to determine the difference between wound cleansing techniques, irrigation and swabbing, in relation to bleeding, pain, infection, necrotic tissue and exudate in non-infected chronic wounds including pressure injuries, venous and arterial leg ulcers and diabetic foot ulcers. Methods: A systematic search of the electronic databases Ovid Medline, Cochrane Database of Systematic Reviews, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and EMBASE was performed to identify all relevant literature in English. The search also included systematic reviews as a method to obtain additional potential citations by manually searching the reference lists. Included studies were assessed for methodological quality using the Cochrane Risk of Bias Tool. Results: One study met eligibility criteria. Two hundred fifty six patients with wounds healing via secondary intention (n = 256) were included. Wound cleansing via swabbing technique was associated with increased perception of pain and increased rates of infection when compared to the irrigation group (93.4% versus 84.2% p = 0.02 and 5.2% versus 3.3% p = 0.44, respectively). Only a small proportion of this sample met the inclusion criteria, so the results are not considered externally valid. Conclusion: Wound cleansing remains a controversial topic. Despite calls for further research, there continues to remain a large gap in evidence to guide practice. Irrigation continues to replace swabbing in the management of chronic wounds, although evidence of improved outcomes is virtually nonexistent. Although the one study identified was of sound methodological quality, chronic wounds accounted for only a small percentage of the sample. Therefore, results are not generalizable to those with chronic wounds. Further research is needed to determine the effectiveness of basic wound cleansing techniques before considering more costly products. Highlights: Wound cleansing practice continues to be influenced by expert opinion alone. Inadequate wound cleansing can lead to biofilm and wound chronicity. Studies continue to be lacking in the comparison of cleansing techniques. Lack of research has allowed industry to introduce more costly, advanced products.